Foldable and transportable disaster relief shelters - Mohd Afiq Syafiq b Md Noor, Mohd Afiq Syafiq (2010)
This report is intended to design the safest and easy to erect and store the shelter. The ease of transportation is also one of the main concerns on designing the shelter.